Analysis of Implementation of Five-Day School Policy in North Sumatera Province (Inovasi, 2026)
This study aim to analyse the implementation of the five-day school policy at the high school and vocational school in North Sumatera Province, which will be implemented in 2025/2026 academic year. Using a qualitative approach with a descriptive case study method, this study involved various stakeholders, including school principals, teachers, student and parents. Data was collected through questionnaires administered to 64,063 respondens and document studies. The results of study show polarized perceptions : while teachers and parents support this policy for the sake of character building and performance efficiency, student show high resistance due to physical and mental fatigue (burnout). SWOT analysis identifies that success of the policy is highly dependent on infrastructure readiness and a more humanistics curriculum reconstruction.